Preliminary Study on Optimization Carbon Fibre Reinforced Polymer as Wrapping Structure at 90-degree Elbows Piping System via Finite Element Analysis - Subba Rao, Narendraan Rao; Tajul Arifin, Ahmad Mubarak; Mohammad, Mazian; Taib, Ishkrizat; M. Letchumanan, Shaktivell (semarak ilmu, 2024)
Carbon Fiber Reinforced Polymer (CFRP) considered as unique material as it is proven have the best mechanical properties which can be used as a wrapping. This composite material will be evaluated as a wrapping material using SolidWork version 2021 software. Elbow has been chosen as component to be wrapped as it is one of the most critical parts in a pipeline system. Thus, this research focuses on 90-degree butt welded elbows. The study evaluated different lamination and thickness of CFRP as a wrapping framework for elbows. Static analysis also was stimulated to analyze the stress and strain exerted on elbows at extrados location. Based on static analysis simulation from SolidWork software, lamination orientation of (0º) with 6 layers exhibit lowest stress for all the pressure tested ranging from 0.86MPa to 19.65MPa for 90-degree defected elbow at extrados location. Besides, comparing CFRP and Glass Fibre Reinforced Polymer (GFRP), CFRP showed it able to reduce stress compared to GFRP when tested on the same defected elbow. Lastly, the flow simulation in CFD showed there were no leakages especially on defected area and no sudden changes on pressure, velocity, and temperature.